Employee Commitment, Motivation, and Engagement: Exploring the Links - Meyer, John (Oxford University Press, 2014)
Commitments in the workplace can take different forms and be directed at different targets (e.g., organization, teams, goals). As a force that binds individuals to a course of action of relevance to the target, commitment has motivational properties, but it is only recently that theories of commitment and motivation have been integrated. This chapter traces the development of the three-component model of commitment and highlights the important role played by self-determination theory in its integration into the work motivation literature. It also describes how the three-component model and self-determination theory have been combined to serve as the basis for an evidence-based model of employee engagement. The chapter concludes by identifying directions for future research.